Jazz Dance on Menopausal Symptoms and Psychological Aspects: A Randomized Clinical Trial Pilot Study With Follow-Up - Martins J.B.B.* (2024)
© 2024 SHAPE America.To analyze the short-term (one month intervention and post-intervention) and long-term (six-month follow-up) effects of Jazz Dance on menopausal symptoms (somatic, psychological and urogenital), in addition to the psychological aspects in specific (anxiety, depression, mood, stress, and aging perspective), compared to the control group of menopausal women. Randomized clinical trial with early postmenopausal women divided into two groups: Jazz Dance Intervention Group (GIDJ) (n = 23), and control group (CG) (n = 24). The physical exercise group received interventions of two weekly sessions of 60 minutes each, for 16 weeks. The control group received monthly calls, educational lectures, and maintained their usual activities during the intervention period. Assessments with all participants occurred at baseline, after the 1st month, after the interventions, and at the six-month follow-up. The evaluations are assessed by questionnaires and include menopausal symptoms (Menopause Rating Scale), depressive and anxiety symptoms (Anxiety and Depression Scale), stress (Perceived Stress Scale), mood (Brunel Mood Scale), and aging perspective (Sheppard Inventory). There was a significant improvement in GIDJ outcomes post-intervention, such as menopausal symptoms (p =.001), psychological aspects (anxiety (p = <.001), depression (p =.016) and stress (p =.030)); in the integrity domain (p =.011) for the aging perspective, and in the confusion (p =.028) and vigor (p =.044) domains for mood. Furthermore, the CG showed significant improvements in the happiness domain at one month of intervention (p =.043) from the perspective of aging. Jazz Dance is effective in treating symptoms of menopause, depression, anxiety and stress, especially with an intervention of at least 16 weeks duration.